Assessment of shutdown dose rates in the ITER Collective Thomson Scattering system and in equatorial port plug 12. (1st December 2021) - Chambon, A.; Luís, R.; Klinkby, E.; Nietiadi, Y.; Rechena, D.; Gonçalves, B.; Jessen, M.; Korsholm, S.B.; Larsen, A.W.; Lauritzen, B.; Rasmussen, J.; Salewski, M.; et al.
Abstract: The ITER Collective Thomson Scattering (CTS) system will be the main diagnostic responsible for measuring the velocity distribution function of fusion-born alpha particles in the plasma. As the CTS diagnostic is integrated in the equatorial port plug 12 (drawer 3), with direct apertures to the port interspace where maintenance hands-on operation will be carried out, it is essential to assess the shutdown dose rates (SDDR) in these maintenance areas. In this work, the D1S-UNED3.1.4 Monte-Carlo transport code, based on the implementation of the direct-one-step methodology in MCNP5 v1.60, was used to estimate the dose rate level 12 days (10 6 s) after shutdown in the port interspace. The results show that the CTS system does not contribute significantly to the SDDR in the area where hands-on maintenance is foreseen with contribution to dose rates less than 1 µSv/h. This is consistent with previous estimates, although with the most recent model of the CTS design there is a slight increase of the SDDR values. This deviation can be attributed to design changes and improved shielding modelling and/or most importantly, to statistical fluctuations of the D1S simulations. From a neutronics point of view, the increase in the SDDR falls within the range of the statistical fluctuations, and the design is still compliant with the radiation safety ALARA principle aiming at minimizing radiation doses, and there is no requirement for further design optimizations.